Revictimization in the Age of Social Media: A Feminist Criminological Analysis of Revenge Porn in Indonesia - Dahlan, Rudiyanto; Fathussalam, Muhammad Fikri; Panjaitan, Juniper Dame (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study examines the issue of women's revictimization in the realm of technology-facilitated sexual violence, focusing on revenge porn and blackmail. Female victims are coerced into maintaining a sexual relationship with the offender—often a current or former partner—under the threat of having intimate videos shared on social media. This situation leads to severe psychological effects, such as depression, social ostracism, reluctance to report to authorities, and victim blaming. The research seeks to offer a comprehensive understanding of the revictimization women face and the protective measures that can be implemented through legal frameworks and social strategies. Employing a descriptive qualitative research method, data was gathered through in-depth interviews with three victims of revenge porn. Findings indicate that media significantly worsens the victims' plight by spreading sexually exploitative content. The study also suggests human rights-based protection policies and strategies, emphasizing the need for public education to combat digital sexual violence.